Interpretation of a verbal-visual communication - Habrajska, Grażyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
In contemporary internet-dominated everyday life, ever more often one faces communications which utilise both verbal (words) and iconic (images) codes. In the article, I analyse two types of said communications: advertisements and memes. Both advertising content and memes belong to journalistic discourse. Therefore, one can analyse them using the same methods as verbal opinion texts, which require one to specify the situational background, the specific situation, the persuasive/ propaganda aim, and to standardise arguments. At the same time, memes are included in comical discourse, to analyse which it is necessary to be able to juxtapose the actual image with the presented image.